Analisis Penerapan Program Pencegahan dan Pengendalian Infeksi di Ruang Rawat Inap RSUD Tebet Tahun 2017 - Madjid, Tetyana (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2017)
The focus of this research is indentifying infection prevention and control program in Tebet hospital through observation of nursing action on infusion, bandage, injecting and waste management, and indentifying nurse’s characteristics, policies, facilities, monitoring and reporting of infection. This research using qualitative and quantitative approach. Unit analysis of this research is 105 of actions mentioned above by all nurses in the inpatient room. The results of this study show that most of the actions performed by the nurses were good, analysis with univariat, bivariat and logistic regression of multivariat. The most affecting variables is the reporting of infection. Suggestions for hospitals is to improve organizational structure, assign full timen IPCN nurses and improve training effectiveness